A MULTIPLE REGRESSION ANALYSIS OF TOKOPEDIA E-COMMERCE USERS’ PURCHASING DECISIONS - Stella Junianti; Henilia Yulita; Michael Christian (Proceeding of International Conference on Entrepreneurship (IConEnt), 2022)
The goal of this research was to investigate the impact of word of mouth and brand image on purchasing decisions on the e-commerce site Tokopedia. The data used in this study is primary data collected through a questionnaire on Tokopedia e-commerce users using a purposive sampling technique. Tokopedia is one of the most popular online shopping platforms in Indonesia. Consumers will consider several factors when making purchasing decisions, including reviews from previous customers. Furthermore, consumers consider the platform's brand image. This study employs the uses and gratification theory as a foundation for communication thinking with a quantitative approach, analyzing data obtained from questionnaires distributed by the researchers and processed using the SPSS version 26 application. The findings of this study show that word of mouth has an impact on purchasing decisions and brand image. This can be demonstrated using the T and F tests to determine whether word-of-mouth and brand image influence purchasing decisions on Tokopedia's online store.